4th International Conference of Photography and Theory (Icpt2016) - (:unkn) unknown (My University, 2026)
4th International Conference of Photography and Theory (Icpt2016) 2016 Photography and the Everyday The Nicosia Municipal Arts Centre, Associated with the Pierides Foundation [Nimac] Nicosia, Cyprus. 2-4 December, 2016 “Birth Certificate”: The Transference of an Intimate, Private Photograph into a Public Site of Mediterranean Silent History.”